Studing Optical and Electrical Properties of Bi203 Thin Filam for Optoelectronic Applications - Zalzala, Hashim A R; Muhson, Basheer Y; Ahmed, Muhnad A (Al-Nahrain Journal of Science, 2018)
Bismuth oxide thin film has been prepared on KB7 glass substrates using slow thermal oxidizing bismuth films of thickness (80 nm) in air at 473 K for 10 hours. The structure Characterization of the film was carried out with XRD. The results of XRD technique shows that all samples have a polycrystalline and multiphase (α-Bi2O3 and β-Bi2O3). the optical transmittance in visible region was investigated. The optical energy gap (Eg = 2.5 eV) determined from absorption specter. The dark resistivity and thermoelectric power (TEP) were investigated. The electrical resistivity is of the order of 106 ohm-cm. and the thin film n-type semiconductor It was found that the activation energy Ea